A Survey on Sentimental Analysis Techniques - FathimaChinnaRani, K.Lino; Kasthuri, M; PraveenKumar, N.Solomon (International Journal of Computer Sciences and Engineering, 2025)
Sentiment analysis is one of the fastest developing research areas in computer science, which is helpful to analyze people’s opinions, sentiments, evaluations, attitudes and emotions from written language. It is widely studied in data mining, web mining, and text mining. This survey paper presents a comprehensive study on various recently used sentiment analysis techniques. The main target of this survey paper is to give full image of sentimental analysis techniques and the related field with brief details. The cluster of datasets given as an input and the accuracy level is checked by using discourse relations. The limitations and features are also discussed